Análisis de la recaudación de impuestos prediales urbanos y rurales y su impacto en la distribución económico social en los habitantes del cantón Mocache. año 2015 - Carrera Chico, Franklin Edison (2016)
This research was performed in the Decentralized Autonomous Municipal Government of the canton Mocache, province of Los Ríos. The goal was to conduct an analysis of the property taxes revenues for the next biennium. It was considered for the first specific objective of this research: comparative analysis affected by the budget for the prioritization of social public works items. A matrix was developed detailing contributions and own income, taken from the Institutional and Organizational Framework. For the second objective: Describe the new calculation of property taxes rates according to the sector and commercial influence, for a full and effective cadastral reform and own incomes and achieve a maximum level of local development in the canton. The following research methods were used: Deductive, Inductive and Analytical Synthetic, primary source information obtained from the Department of Valuation and Land extracted; the techniques used were direct observation and surveys were conducted in urban and rural areas, an interview with the Mayor Mr. Leandro Rodríguez Ullón, In conclusion, the resident´s research indicated that drinking water is the one that won a share of 46% as a component of the budget items, and the works carried out by internal budget of GAD Municipal Mocache are sidewalks and curbs and park creation and adaptation of the canton. Management in obtaining state budget is below the POA, conducted by the municipality for the year 2015, obtaining resources has been discontinuously and slowed, covering a relatively low percentage of works by foreign-run ends with the development of the matrix of priority projects that are near completion, the incidence produces real impact allowing achieve a maximum level of local development in the canton Mocache. Keywords: Analysis, Revenue, Property Tax, Social Economic Distribution.